2011
DOI: 10.1161/circulationaha.110.971853
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids Prevent Pressure Overload–Induced Cardiac Fibrosis Through Activation of Cyclic GMP/Protein Kinase G Signaling in Cardiac Fibroblasts

Abstract: Background— Omega-3 polyunsaturated fatty acids (eicosapentaenoic acid and docosahexaenoic acid) from fish oil ameliorate cardiovascular diseases. However, little is known about the effects of ω-3 polyunsaturated fatty acids on cardiac fibrosis, a major cause of diastolic dysfunction and heart failure. The present study assessed the effects of ω-3 polyunsaturated fatty acids on cardiac fibrosis. Methods and Results— We assessed left ventricular fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
141
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 32 publications
9
141
0
3
Order By: Relevance
“…The n-3 polyunsaturated fatty acid supplementation attenuated cardiac hypertrophy and fibrosis and prevented upregulation of genes associated with heart failure in rats. 15,16 In our subjects eating a reduced-carbohydrate diet, sucrose ingestion decreased whereas polyunsaturated fatty acid ingestion increased relative to total energy intake. However, these positive changes in dietary composition may have been counterbalanced by increased saturated fatty acid ingestion.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The n-3 polyunsaturated fatty acid supplementation attenuated cardiac hypertrophy and fibrosis and prevented upregulation of genes associated with heart failure in rats. 15,16 In our subjects eating a reduced-carbohydrate diet, sucrose ingestion decreased whereas polyunsaturated fatty acid ingestion increased relative to total energy intake. However, these positive changes in dietary composition may have been counterbalanced by increased saturated fatty acid ingestion.…”
Section: Discussionmentioning
confidence: 82%
“…We suggest that the limited impact of macronutrient composition on LV mass in patients may be explained by the modest carbohydrate or fat restriction compared to dietary manipulations in rodents. 12,13,16 Species differences in the susceptibility to dietary interventions also may be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This is supported by several mechanisms: (i) favorable changes in cell membrane lipid composition; 6 (ii) modulation of soluble and cellular inflammatory responses; 7 (iii) modulation of the coagulation cascade, 8 and (iv) production of nitric oxide. 9 The fatty acid profile of the red cell membrane from SCD patients is intrinsically different from that of healthy controls, with a relative increase in the ratio of ω-6 to ω-3 PUFA. 10,11 Sickle erythrocytes have increased ω-6-derived arachidonic acid (20:4n6) and decreased eicosapentaenoic acid (20:5n3) and docosahexaenoic acid (22:6n3).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that n-3 PUFA increases the expression and activation of eNOS, leading to vasodilation 17) . Furthermore, the EPA-induced translocation of eNOS from caveolin in the cell membrane to the cytosol results in the enhancement and activation of the eNOS system and may a cause of EPA-induced vasodilation 18) .…”
Section: Discussionmentioning
confidence: 99%